DFT exchange: sharing perspectives on the workhorse of quantum chemistry and materials science. Issue 47 (21st October 2022) - Teale, Andrew M.; Helgaker, Trygve; Savin, Andreas; Adamo, Carlo; Aradi, Bálint; Arbuznikov, Alexei V.; Ayers, Paul W.; Baerends, Evert Jan; Barone, Vincenzo; Calaminici, Patrizia; Cancès, Eric; Carter, Emily A.; et al.
Abstract : In this paper, the history, present status, and future of density-functional theory (DFT) is informally reviewed and discussed by 70 workers in the field, including molecular scientists, materials scientists, method developers and practitioners. Abstract : In this paper, the history, present status, and future of density-functional theory (DFT) is informally reviewed and discussed by 70 workers in the field, including molecular scientists, materials scientists, method developers and practitioners. The format of the paper is that of a roundtable discussion, in which the participants express and exchange views on DFT in the form of 302 individual contributions, formulated as responses to a preset list of 26 questions. Supported by a bibliography of 777 entries, the paper represents a broad snapshot of DFT, anno 2022.